Peningkatan Kapasitas Produksi dan Kualitas Produk Nugget Kaila Rasa Melalui Program Pemberdayaan Kelompok Usaha - Yunita Andi Kemalasari; Martdian Ratna Sari; Fitri Safira; Bram Manuel Banuarta Sianturi (I-Com: Indonesian Community Journal, 2024)
Nesya Jaya Rasa Nugget is a home business group that has been established since 2018, in Rumpin District, Bogor. On average, 1 production can produce 50 balls or around 1,250 packs of nuggets. The purpose of this community service and empowerment program is to increase production capacity and product quality including product packaging. This community service and empowerment program begins with a needs analysis through partner surveys and observations, followed by determining an empowerment program according to needs, then carrying out training and mentoring related to product capacity and quality through the provision of appropriate tools/technology to increase the effectiveness of production time. The results obtained from this program are an increase in the knowledge and skills of business groups related to maintaining product quality through cleanliness of production rooms, increasing production capacity and quality through the use of appropriate technology and the use of attractive product packaging.